2001
DOI: 10.1108/13552540110395538
|View full text |Cite
|
Sign up to set email alerts
|

Computer aided decision support for fused deposition modeling

Abstract: Parts formed using fused deposition modeling (FDM) can vary significantly in quality depending on the manufacturing process plan. Altering the plan profoundly affects the character of the resulting part. Although the designer and the machine user may have preferences regarding the part build and the relative importance of build outcomes such as production speed, dimensional accuracy, and surface quality, setting process variables to ensure desired results is a complex task. A multi‐objective decision support s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 20 publications
0
34
0
2
Order By: Relevance
“…Within the CAO software, the soft kill option (removing non-efficient material) and finite element analysis analysis of the model were performed so as to obtain an optimal design. Other technical aids include those proposed by Ziemian and Crawn (2001) who developed a decision support tool for Fused Deposition Modelling systems to guide users for the most optimal build settings. Pandey et al (2007) suggested that part deposition orientation is a major factor for AM as it effects build time, support structure, dimensional accuracy, surface finish and cost of the end product.…”
Section: Previous Workmentioning
confidence: 99%
“…Within the CAO software, the soft kill option (removing non-efficient material) and finite element analysis analysis of the model were performed so as to obtain an optimal design. Other technical aids include those proposed by Ziemian and Crawn (2001) who developed a decision support tool for Fused Deposition Modelling systems to guide users for the most optimal build settings. Pandey et al (2007) suggested that part deposition orientation is a major factor for AM as it effects build time, support structure, dimensional accuracy, surface finish and cost of the end product.…”
Section: Previous Workmentioning
confidence: 99%
“…Therefore, in the recent years several research works have been published (e.g., [5][6][7][8]) for improving specific attributes of parts obtained by FDM such as surface finishing or dimensional accuracy. These works modify characteristic parameters of the process, such as the thickness of each layer, orientation of the piece or structure of filling material.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the use of the term "Fused Deposition Modeling" is found with greater relevance in quantity as well as in the number of quotes, for example, we see that [15], [16] refers with this term to a study of Surface finishing vs deposition time of melted material, [17] refers to it for a study of mechanical featuring of manufactured parts using this technology, [18], [19] in research for the use of polymethylmethacrylate through 3D printing for the manufacture of implants using FDM technology, and [20] develops a support system of multiobjective decisions to assist users of FDM processes to select the setting variables to achieve specific targets in regard to the characteristics of the parts of the piece to be printed. Finally, referencing the technology like "Fused deposition modeling" for the design and construction of a 3D printer [21], [22].…”
Section: A Exploration Of Fdm Technology In Literaturementioning
confidence: 99%